Table of Contents (Law, State and Telecommunications Review, 2019)
Dear Reader, We are pleased to introduce the eleventh volume of the Law, State and Telecommunications Review (LSTR).In this issue, the journal published a number of original articles on topics relevant to telecommunications from a myriad of interdisciplinary perspectives.We are delighted to include articles on public choice and the deregulation movement in the European Telecommunications, UK postal rule applied to electronic contracts, IoT spectral demand in Mexico, use of ICT in police districts in Peru, competition in the traditional telecommunications market and the OTT role, disruptive models for the telecom operators in the new digital arena, filtering technique in wireless sensors, metamaterials absorber for stealth applications, telecommunication network deployment algorithm, fractal antenna parameters for reception of digital terrestrial television signals in the UHF band, integrated purchasing and banking data protection in the context of the Directive (EU) 2015/2366, effectiveness of French contract law on OTTs, liability legal regime applicable to the technical intermediaries in the European and French Law, judicial control of the telecom regulatory agency’s decision-making power in long-distance-like calls in Brazil, and the origin of digital inequalities in the city of Sao Paulo.For future issues, we will continue to publish articles on all relevant areas of telecommunications.We hope you have enjoyed reading this issue looking forward to a second issue of this eleventh volume to be released on October 2019. Sincerely, Prof. Marcio Iorio AranhaEditor-in-Chief, The Law, State and Telecommunications ReviewOn behalf of the Editorial Board